The Community College in Comparative and Historical Perspective: The Development of the College Concept in British Columbia - Dennison, John D. (Canadian Journal of Higher Education, 1979)
The paper is concerned with an examination of one alternative model for post-compulsory education, the community college, as it has developed in British Columbia. Attention is given to the social and historical context in which the college idea developed, the forces which lead to its establishment and the particular form of institution which emerged. Data, produced from research studies, are presented to indicate the extent to which the college has attained some of its objectives. The paper concludes with a discussion of the major problems and issues which the community colleges must face in the future. Wherever appropriate, comparisons are made with traditional systems of post compulsory education.